Postgastrular zen expression is required to develop distinct amniotic and serosal epithelia in the scuttle fly Megaselia - Rafiqi, Abdul Matteen; Lemke, Steffen; Schmidt-Ott, Urs (Developmental biology, 2010)
The amnioserosa is an extraembryonic epithelium that evolved in higher cyclorrhaphan flies from distinct serosal and amniotic epithelia. The underlying genetic mechanism of this evolutionary transition is unknown. Amnioserosa development of Drosophila correlates with novel expression characteristics of the homeobox gene zerknüllt (zen), including a broad zen expression domain in the syncytial blastoderm and the complete absence of postgastrular zen expression. Here we examine the functional significance of these features by altering the activity profile of zen in Megaselia (a lower cyclorrhaphan fly with distinct serosal and amniotic epithelia) and Drosophila, and by examining in Megaselia the function of u-shaped group (ush-group) genes, which in Drosophila maintain the amnioserosa after gastrulation when zen is no longer expressed. In Megaselia, loss of postgastrular zen expression abrogates serosa development but allows amnion development. Ectopic expression of zen in early Megaselia embryos allows serosa formation but perturbs amnion development. Megaselia homologues of u-shaped group genes are not essential for serosa formation but mediate germband retraction and dorsal closure. Finally, ectopic postgastrular zen expression in Drosophila causes an enlargement of amnioserosa cells and interferes with the morphogenetic functions of the amnioserosa. Our results suggest that the origin of the amnioserosa involved the loss of postgastrular zen expression from extraembryonic tissue, that the early broad expression domain of Drosophila zen evolved afterwards, and that the ush-group genes ancestrally played a role in morphogenetic functions of the amnion.